The effect of ionizing radiation on the subcellular localization and kinase activity of protein kinase CK2 in human non-small cell lung cancer cells. (2nd November 2019) - Li, Qianwen; Li, Ke; Zhang, Sheng; Zhou, Yu; Hong, Jiaxin; Zhou, Xiaoshu; Li, Zhenyu; Wu, Bian; Wu, Gang; Meng, Rui
Abstract: Protein kinase CK2 is a ubiquitously expressed kinase in eukaryotes, which is known to phosphorylate many protein substrates. Because CK2 is involved in the regulation of various signaling pathways, we wondered whether CK2 participated in the regulation of ionizing radiation (IR) induced biological process. In this study, we investigated the effect of IR on the subcellular localization and kinase activity in human non-small cell lung cancer (NSCLC) cells. Immunofluorescent results showed that CK2 subunits shuttle into the nucleus mostly beginning 1 h after IR and lasting more than 6 h. We also conducted in vitro kinase assay and observed an increase in CK2 kinase activity at 6 h after IR. Furthermore, an increase in S phase was observed at 6 h after IR. Colony formation assay results demonstrated that CK2 inhibitor CX-4945 significantly enhanced the effect of irradiation in NSCLC cells. These results indicated that CK2 may be implicated in the regulation of IR-induced biological process.